Islamic Republic of Iran : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the role of the financial sector and Islamic finance in the development of Iran's economic strategy is discussed. The structure and governance aspects of Iran's financial system are explained by means of equity finance and the banking sector. The role of Iron Mercantile Exchange (IME) is explained under equity finance. The performance and soundness of banks in Iran are analyzed. Finally, a framework for Iran's financial stability is explained. Financial, operational restructuring, and international experiences of corporate restructuring are also outlined.